Gut microbiota profiling of pediatric nonalcoholic fatty liver disease and obese patients unveiled by an integrated meta‐omics‐based approach. Issue 2 (2nd June 2016) - Del Chierico, Federica; Nobili, Valerio; Vernocchi, Pamela; Russo, Alessandra; De Stefanis, Cristiano; Gnani, Daniela; Furlanello, Cesare; Zandonà, Alessandro; Paci, Paola; Capuani, Giorgio; Dallapiccola, Bruno; Miccheli, Alfredo; et al.
Abstract : There is evidence that nonalcoholic fatty liver disease (NAFLD) is affected by gut microbiota. Therefore, we investigated its modifications in pediatric NAFLD patients using targeted metagenomics and metabolomics. Stools were collected from 61 consecutive patients diagnosed with nonalcoholic fatty liver (NAFL), nonalcoholic steatohepatitis (NASH), or obesity and 54 healthy controls (CTRLs), matched in a case‐control fashion. Operational taxonomic units were pyrosequenced targeting 16S ribosomal RNA and volatile organic compounds determined by solid‐phase microextraction gas chromatography‐mass spectrometry. The α‐diversity was highest in CTRLs, followed by obese, NASH, and NAFL patients; and β‐diversity distinguished between patients and CTRLs but not NAFL and NASH. Compared to CTRLs, in NAFLD patients Actinobacteria were significantly increased and Bacteroidetes reduced. There were no significant differences among the NAFL, NASH, and obese groups. Overall NAFLD patients had increased levels of Bradyrhizobium, Anaerococcus, Peptoniphilus, Propionibacterium acnes, Dorea, and Ruminococcus and reduced proportions of Oscillospira and Rikenellaceae compared to CTRLs. After reducing metagenomics and metabolomics data dimensionality, multivariate analyses indicated a decrease of Oscillospira in NAFL and NASH groups and increases of Ruminococcus, Blautia, and Dorea in NASH patients compared to CTRLs. Of the 292 volatile organic compounds, 26 were up‐regulated and 2 down‐regulated in NAFLD patients. Multivariate analyses found that combination of Oscillospira, Rickenellaceae, Parabacteroides, Bacteroides fragilis, Sutterella, Lachnospiraceae, 4‐methyl‐2‐pentanone, 1‐butanol, and 2‐butanone could discriminate NAFLD patients from CTRLs. Univariate analyses found significantly lower levels of Oscillospira and higher levels of 1‐pentanol and 2‐butanone in NAFL patients compared to CTRLs. In NASH, lower levels of Oscillospira were associated with higher abundance of Dorea and Ruminococcus and higher levels of 2‐butanone and 4‐methyl‐2‐pentanone compared to CTRLs. Conclusion: An Oscillospira decrease coupled to a 2‐butanone up‐regulation and increases in Ruminococcus and Dorea were identified as gut microbiota signatures of NAFL onset and NAFL‐NASH progression, respectively. (Hepatology 2017;65:451‐464)